ORGANISATIONAL TRANSFORMATION AND SUSTAINABILITY OF RADIO STATIONS IN ENUGU STATE, NIGERIA (Journal of the Management Sciences, 2025)
In a rapidly evolving media landscape, characterized by technological advancements and shifting audience preferences, the need for radio stations to adapt and transform is critical for their survival and effectiveness. This study examines the effect of organizational transformation and sustainability within radio stations in Enugu State, Nigeria. The research examines four specific dimensions of organizational transformation strategic realignment, service quality, cultural shift, and restructuring and their respective influence on their local communities. Utilizing a survey research design and targeting a population of 400 management, technical, administrative, marketing, and on-air staff across five selected radio stations. A sample size of 200 respondents was determined using Taro Yamane's formula. Data were collected through structured questionnaires. The findings reveal that strategic realignment significantly enhances environmental resilience, establishing it as essential for adapting to external pressures. Additionally, service quality was found to positively influence business continuity, underlining its role in maintaining operational effectiveness during disruptions. A cultural shift significantly contributes to functional durability, highlighting the importance of inclusivity and relevance in programming. Lastly, restructuring demonstrated a strong positive influence on business viability, indicating its necessity for long-term financial sustainability. These insights contribute to the broader discourse on operational transformations in the media sector, offering strategic recommendations for radio stations in Enugu State to achieve sustainable practices and maintain relevance in an increasingly competitive environment.
Keywords: Organizational Transformation; Strategic Realignment; Service Quality; Sustainability; Environmental Resilience; Business Continuity